Determinants of the Difference between Actual Cost and Indonesian Case Based Groups (INA-CBGs) Reimbursement for Birth Delivery at Hospitals in Mataram, West Nusa Tenggara - Ismiana, Baiq Holisatul; Tamtomo, Didik; Sulaeman, Endang Sutisna (Journal of Health Policy and Management, 2019)
Background: Health is the part of the economic and social development of the state. The application of the BPJS Health national social security system in Indonesia is one of the government's efforts to provide health financing protection for all citizens and prevent catastrophic health expenditures. Hospitals as providers of secondary or tertiary health services often suffer losses because the payment system from BPJS Kesehatan uses a case-based payment method or INA-CBGs. This study aimed to examine the factors that influence the difference in rates between INA-CBGs rates and real hospital rates in labor cases.Subjects and Method: This was an analytic observational study with a cross-sectional design.  The study was carried out in Mataram and Siti Hajar Mataram Islamic hospitals, Mataram, West Nusa Tenggara, in May 2019. A sample of 200 postpartum women was selected by stratified random sampling. The dependent variable was the difference between real cost and INA-CBGs reimbursement. The independent variables were the type of hospital, class of treatment, type of birth delivery, length of stay, and severity disease. The data were collected from the medical record and analyzed by a multiple linear regression run on Stata 13.Results: Difference between real cost and INA-CBGs tariff of birth delivery reimbursement was negatively affected by type III of class treatment (b = -390,725; 95% CI= -790,082 to 8,631; p= 0,055), section caesarean (b= -1,429,648; 95% CI= -1,811,275 to -1,048,022; p <0.001), length of stay (b= -211,912; CI (95%) = -427,786 to 3,960; p = 0.054), moderate severity (b= -114,028; 95% CIi= -507,057 to 279,000; p = 0.568), and the high level of severity (b = -1,735,612; CI (95%) = -3,482,347 to 11,123; p = 0.051). The INA-CBGs rate difference and RS real rates of labor cases decreased due to the classification of private hospitals (b = 281,021; CI (95%) = -73,054 to 635,097; p = 0,119), treatment class II (b = 8,736; CI (95 %) = -392,068 to 409,541; p = 0.966).Conclusion: The difference in rates between INA-CBGs rates and hospital real rates in childbirth cases would increase if it serves treatment class III, type of cesarean delivery, care days which are longer, and moderate or severe severity. The difference in rates between INA-CBGs rates and hospital real rates in childbirth cases can decrease in services at private hospitals and serve treatment classes II.Keywords: INA-CBGs rates, hospital real rates, labor costs.                                                                            Correspondence: Baiq Holisatul Ismiana. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, Surakarta 57126, Jawa Tengah, Indonesia. Email: baiqholis26@gmail.com. Mobile: +6287739031046.Journal of Health Policy and Management (2019), 4(3): 161-169https://doi.org/10.26911/thejhpm.2019.04.03.03